2016
DOI: 10.1093/toxsci/kfv332
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Exposure to Paracetamol and Aniline Impairs Female Reproductive Development by Reducing Follicle Reserves and Fertility

Abstract: Studies report that fetal exposure to paracetamol/acetaminophen by maternal consumption can interfere with male reproductive development. Moreover, recent biomonitoring data report widespread presence of paracetamol in German and Danish populations, suggesting exposure via secondary (nonpharmaceutical) sources, such as metabolic conversion from the ubiquitous industrial compound aniline. In this study, we investigated the extent to which paracetamol and aniline can interfere with female reproductive developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 55 publications
1
49
2
Order By: Relevance
“…9). Similar effects on gonad development and reproductive health of F0 adult female rodents have been described after exposure to high doses of APAP or indomethacin (26,27). However, fertility of adult male rats (26) and sperm parameters in mice (25) were not altered by exposure in utero to these drugs.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…9). Similar effects on gonad development and reproductive health of F0 adult female rodents have been described after exposure to high doses of APAP or indomethacin (26,27). However, fertility of adult male rats (26) and sperm parameters in mice (25) were not altered by exposure in utero to these drugs.…”
Section: Discussionmentioning
confidence: 63%
“…Similarly, in vivo administration of APAP or indomethacin to pregnant rats during embryogenesis decreases the number of fetal germ cells and accelerates their embryonic differentiation but does not affect the fertility of adult male rats (26). In females, the number of primordial germ cells is reduced (27) and meiotic entry delayed (26) in fetal mouse and rat ovaries, respectively, leading to a decreased number of follicles in adult mouse ovaries (27) and reduced fertility in F1 and F2 rat females (26). In addition, exposure of ex vivo cultures of human embryonic ovaries to IBU induces a decrease in the germ-cell pool due to a decrease in their proliferation and an increase in their apoptosis (28).…”
mentioning
confidence: 99%
“…This effect is a result of inhibition of prostaglandin biosynthesis playing role in the testosterone synthesis in fetal testes (Gupta and Goldaman, 1986; Gupta, 1989). Nevertheless it seems, that paracetamol and other mild analgesics, regardless of gender, causes a decline in reproductive health (Dean et al, 2016; Holm et al, 2016). Recent data reported that in rodents the exposure to paracetamol or its precursor – aniline during pregnancy impairs also female reproductive development and fertility.…”
Section: Introductionmentioning
confidence: 99%
“…Recent data reported that in rodents the exposure to paracetamol or its precursor – aniline during pregnancy impairs also female reproductive development and fertility. These chemicals can decrease female anogenital development, reducing the reserve of primordial and growing follicles and the number of gonocytes (Holm et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental studies have suggested that acetaminophen exhibits endocrine disruptive effects and in utero exposure could affect fetal development . Intrauterine exposure to acetaminophen inhibited fetal testosterone production in ex vivo fetal rat testes , while female mouse fetuses exposed to acetaminophen showed perturbed proliferation of the primordial germ cells, resulting in a reduction of ovarian follicle reserves . Epidemiological studies have also found that prenatal acetaminophen exposure was associated with increased occurrence of cryptorchidism and shorter anogenital distance in male infants as well as earlier pubertal development in female offspring .…”
Section: Introductionmentioning
confidence: 99%